2015
DOI: 10.1002/pri.1642
|View full text |Cite
|
Sign up to set email alerts
|

Body Posture After Mastectomy: Comparison Between Immediate Breast Reconstruction Versus Mastectomy Alone

Abstract: Women who underwent mastectomy alone, compared with women who underwent immediate breast reconstruction with abdominal flaps, showed differences in the vertical alignment of the trunk, with greater asymmetry between the acromion and greater trochanter, which can mean trunk rotation. No significant differences were found between the two groups in the alignment of the head, shoulders, scapula, or pelvis. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…There is only one study in the literature evaluating the change in body posture based on bony structures in women after mastectomy in comparison with immediate breast reconstruction using special software analyzing digital images. 12 Our observations during breast reconstruction surgeries over the years indicated a contralateral shoulder elevation in women with unilateral mastectomy to compensate for the weight of the missing breast ( Figure 1). We believe that this acquired posture can affect spinal alignment in the long term, because postural changes can cause serious deformity on the spine that leads to scoliosis, which is defined as more than 10 of deviation in structural curves.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is only one study in the literature evaluating the change in body posture based on bony structures in women after mastectomy in comparison with immediate breast reconstruction using special software analyzing digital images. 12 Our observations during breast reconstruction surgeries over the years indicated a contralateral shoulder elevation in women with unilateral mastectomy to compensate for the weight of the missing breast ( Figure 1). We believe that this acquired posture can affect spinal alignment in the long term, because postural changes can cause serious deformity on the spine that leads to scoliosis, which is defined as more than 10 of deviation in structural curves.…”
Section: Introductionmentioning
confidence: 89%
“…There are, indeed, several studies in the literature proving the change in body posture in women after mastectomy. [7][8][9][10][11][12] These reports, however, mostly showed shoulder elevation and ipsilateral inclination of the trunk by using photogrammetry or Moiré topography. There is only one study in the literature evaluating the change in body posture based on bony structures in women after mastectomy in comparison with immediate breast reconstruction using special software analyzing digital images.…”
Section: Introductionmentioning
confidence: 98%
“…A study by Jeong JH, Choi B at al. showed that 3 months after surgery the scoliosis angle was significantly increased in patients undergoing mastectomy for breast cancer compared to women operated on with simultaneous breast reconstruction [ 18 , 19 ]. The number of bilateral (contralateral prophylactic) mastectomies performed in recent years has risen, especially in the United States [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well described that immediate reconstruction after unilateral mastectomy can ameliorate changes in body posture 11 . In an assessment of photographs for 76 women, patients who underwent mastectomy alone had significantly greater change in the vertical alignment of the lateral trunk compared to patients who underwent immediate reconstruction with transverse rectus abdominis myocutaneous (TRAM) flap technique 12 . Jeong et al further characterized the impact of breast reconstruction on spinal curvature, reporting significantly lower postoperative changes in Cobb angle of the thoracic spine in women who underwent immediate reconstruction compared to those who underwent mastectomy alone 7 .…”
Section: Discussionmentioning
confidence: 99%